2019
DOI: 10.3390/molecules24193470
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Study of Farrerol Metabolites Produced In Vivo and In Vitro

Abstract: Although farrerol, a characteristically bioactive constituent of Rhododendron dauricum L., exhibits extensive biological and pharmacological activities (e.g., anti-oxidant, anti-immunogenic, and anti-angiogenic) as well as a high drug development potential, its metabolism remains underexplored. Herein, we employed ultra-high performance liquid chromatography/quadrupole time-of-flight mass spectrometry coupled with multiple data post-processing techniques to rapidly identify farrerol metabolites produced in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This and the UV data correspond to farrerol ( Supplementary Materials ), identified in M. prasina [ 59 ]. Yin, Jintuo et al (2019) presented data that support to our findings [ 61 ]. Several of the very minor peaks appeared to have a farrerol aglycone component, based on the prominent m / z 301 ion in positive ion MS.…”
Section: Resultssupporting
confidence: 90%
“…This and the UV data correspond to farrerol ( Supplementary Materials ), identified in M. prasina [ 59 ]. Yin, Jintuo et al (2019) presented data that support to our findings [ 61 ]. Several of the very minor peaks appeared to have a farrerol aglycone component, based on the prominent m / z 301 ion in positive ion MS.…”
Section: Resultssupporting
confidence: 90%
“…Identified pathologically by angiogenesis, inflammation, and synovial hyperplasia in the synovial membrane that results in pannus formation accompanied by bone loss and extreme cartilage (Rutherford et al, 2017). Yin et al conducted the pharmacokinetic study of the farrerol in rat and in the microsomes using the UHPLC-Q-TOF-MS/MS (Yin et al, 2019). Total 42 metabolites such as bile (20), plasma (12), urine (34), faces (36) were found in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatic tissue microsomes found the 15 metabolites. The major metabolic processes included deoxygenation, oxidation, sulfate conjugation, demethylation, and glucuronide conjugation and other less appropriate pathways include the conjugation of glucose, ketonization, conjugation of N-acetylcysteine, methylation, and N-acetylation (Yin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology and molecular biology studies have shown that flavonoids can reduce the risk of cardiovascular disease in the diet, and that their biological functions may be related to antioxidant effects ( Dludla et al, 2017 ). Farrerol is the main ingredient isolated from the traditional Chinese herbal medicine Manshanhong ( Yin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%